2011
DOI: 10.1007/s00198-011-1740-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum RANKL and RANKL in bone

Abstract: It is now well accepted that the molecule receptor activator of NFκB ligand (RANKL) and osteoprotegerin play key roles in regulating physiological and pathological bone turnover. There are a large number of published reports of circulating RANKL levels in both health and pathology. However, interpretation of these data has been elusive, and the relationship between circulating RANKL and RANKL levels in bone is still not clear. This review explores this subject, documenting the possible origins of circulating R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 60 publications
3
47
1
Order By: Relevance
“…The latter observation for IL-6 is in accordance with the previously observed dual role of IL-6 on osteoclasts [17,22,23]. Although previous reports have shown an inverse relationship between RANKL bone mRNA and serum levels in OA males [37], our results of this correlation analysis did not reach the level of significance. The reason is most likely due to low statistical power as there were only three OA males with serum RANKL levels.…”
Section: Discussionsupporting
confidence: 88%
“…The latter observation for IL-6 is in accordance with the previously observed dual role of IL-6 on osteoclasts [17,22,23]. Although previous reports have shown an inverse relationship between RANKL bone mRNA and serum levels in OA males [37], our results of this correlation analysis did not reach the level of significance. The reason is most likely due to low statistical power as there were only three OA males with serum RANKL levels.…”
Section: Discussionsupporting
confidence: 88%
“…Most commercial kits measure free RANKL, which is w1/1000 of the total serum RANKL. This feature explains that some investigators have reported undetectable levels of RANKL in up to 50% of individuals (43). Moreover, the antibodies may measure different RANKL types of the soluble molecular species of the cytokine (44), a conceivable difficulty given the research profile of the available assays.…”
Section: Other Regulatorsmentioning
confidence: 99%
“…These disorders might be imposed predominantly by the changes occurring directly in tumor tissue, but we cannot ignore the fact that serum levels of RANK/RANKL/OPG components, as well as the level of any other serological marker, cannot be completely determined by the secretion of corresponding protein from tumor cells. It depends on various physiological factors, on probable production of proteins studied by other tissues, and on the presence of concomitant diseases, in particular, osteoporosis and inflammatory processes [14,15].…”
Section: Discussionmentioning
confidence: 99%